Incidental microfilaria in cervical lymph node cytology - Vandana Gite; Maruti Dhakane (Apollo Medicine)
Although filariasis is a major health problem in tropical countries including India, lymph node is an unusual site to present as filarial nodule. It is rare to find microfilaria in lymph node cytology. However, in the absence of clinical features of filariasis, fine-needle aspiration cytology may help in the diagnosis of lymphatic filariasis. We report this case, presented with filarial lymph node mass and diagnosed incidentally on a fine-needle aspiration.